2008
DOI: 10.1002/jbm.a.32104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seeding technique and scaffold material on bone formation in tissue‐engineered constructs

Abstract: The aim of the present study was to test the hypothesis that both scaffold material and the type of cell culturing contribute to the results of in vivo osteogenesis in tissue-engineered constructs in an interactive manner. CaCO3 scaffolds and mineralized collagen scaffolds were seeded with human trabecular bone cells at a density of 5 x 10(6) cells/cm(3) and were left to attach under standard conditions for 24 h. Subsequently, they were submitted to static and dynamic culturing for 14 days (groups III and IV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
2
17
0
2
Order By: Relevance
“…Another four studies evaluated mineralized collagen in in vivo studies, in which two experimental groups were tested in ectopic sites and three in orthotopic sites. [16][17][18][19] The results in ectopic sites are similar to our current findings, as they, indeed, report inflammatory reaction, resulting in complete phagocytosis of the collagen without any signs of bone formation. 17,18 The results in orthotopic sites are inconsistent.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Another four studies evaluated mineralized collagen in in vivo studies, in which two experimental groups were tested in ectopic sites and three in orthotopic sites. [16][17][18][19] The results in ectopic sites are similar to our current findings, as they, indeed, report inflammatory reaction, resulting in complete phagocytosis of the collagen without any signs of bone formation. 17,18 The results in orthotopic sites are inconsistent.…”
Section: Discussionsupporting
confidence: 94%
“…[16][17][18][19] The results in ectopic sites are similar to our current findings, as they, indeed, report inflammatory reaction, resulting in complete phagocytosis of the collagen without any signs of bone formation. 17,18 The results in orthotopic sites are inconsistent. Schliephake et al 19 reported no enhancement of bone formation by mineralized collagen, when implanted in rat mandibles.…”
Section: Discussionsupporting
confidence: 94%
“…A previous study with two of the three scaffold materials, using human trabecular bone cells derived and treated in the same way and seeded under identical seeding density and culturing conditions, showed bone formation after transplantation to ectopic sites. Bone formation in that study was strongly dependent on the scaffold material, because the cells produced considerable amounts of bone in CaCO 3 scaffolds but no bone formation was found in the mineralized collagen scaffolds 29 . The present study appears to contradict these results, in that none of the seeded scaffold materials had a positive effect on bone formation when implanted into non-healing defects in rat mandibles.…”
Section: Discussionmentioning
confidence: 98%
“…In 2009, Schliephake et al cultured constructs of human trabecular bone cells and CaCO 3 scaffolds (pore size: 250-750 µm) or mineralized collagen scaffolds (pore size: 100-200 µm) in vitro for 14 days, and then implanted the constructs in intramuscular pockets or 5-mm mandibular defects in nude rats for six weeks [48,49]. As opposite to the study by Braccini et al, the authors did not found significant differences in bone formation between the constructs cultured under static or dynamic conditions, suggesting that other factors couls play a role in enhancing the bone formation ability of these constructs.…”
Section: Direct Perfusion Bioreactorsmentioning
confidence: 99%